Molecular Epidemiology of Enteric Adenovirus Gastroenteritis in under-Five-Year-Old Children in Iran - Anahita Sanaei Dashti; Pedram Ghahremani; Tayebeh Hashempoor; Abdollah Karimi (Gastroenterology Research and Practice)
Background. Acute gastroenteritis is one of the major sources of morbidity and mortality among young children in developed and developing countries. The aim of this study was to determine the prevalence of human adenovirus- (HAdV-) 40 and HAdV-41 in children hospitalized with gastroenteritis in five different health centers of Iran. Methods. In a cross-sectional epidemiological study, we studied 2682 fecal specimens that were collected from children under the age of 5 years in five educational and therapeutic pediatric centers in Iran from February 2012 to February 2013. Samples were tested for HAdV-40 and HAdV-41, using a specific pair of primers in polymerase chain reaction (PCR) method. Results. HAdV-40 and HAdV-41 were detected in 132 (5.18%) of the patients with diarrhea. A significantly higher prevalence of HAdV-40 and HAdV-41 (58.3%) was observed in children under 12 months of age, compared to other age groups. The male to female ratio was 1.7. Conclusion. The results of this study demonstrated that HAdV-40 and HAdV-41 could be considered etiological agents for acute gastroenteritis among children in Iran. The PCR as a rapid test may increase the chance for a relatively mild course of the disease followed by a complete recovery and avoiding administration of unnecessary antibiotics.